Meningkatkan Pendidikan Melalui Transformasi Digital di Institut Agama Kristen Negeri Manado - Giroth, Lady Grace Jane; Kainde, Quido; Wuwung, Olivia Cherly; Pinontoan, Devis; Martone, Alfi; Putri, Salsabila Pratiwi (Jurnal Pengabdian Literasi Digital Indonesia, 2024)
On July 5, 2024, Pandu Digital North Sulawesi and Institut Agama Kristen Negeri (IAKN) Manado held a digital literacy webinar on digital transformation in education. The event, which was attended by 250 participants both in person and online, became an important platform to explore the role of technology in improving the quality of education, especially at IAKN Manado. In addition, the topics of digital safety and digital media proficiency were also a major focus of discussion. The webinar emphasized that digital transformation in education involves not only the use of technology, but also the wise and safe utilization of technology.